Basal Stem Rot of Oil Palm : Screening System and Bioefficacy of Sterol Biosynthesis Inhibitors Against Ganoderma Boninense - Teh, Kim Sing (1996)
Studies were designed to develop a practical, quick and reliable screening system for basal stem rot (BSR) disease of oil palm using rubber wood inoculum block as an infection foci. Inoculation was performed under non-sterile conditions. 100% success on establishment of disease was achieved on seedlings and immature palms in a relatively short period. G. boninense was able to invade and colonise the oil palm roots without mechanical wounding. Close contact between G. boninense and oil palm seedlings was established In a specially designed plastic container. Disease associated-symptoms were observed within two to three months after inoculation. The typical symptoms observed were the progressive yellowing and desiccation of leaves from the oldest to the youngest and the presence of basidioma. The extend of foliar symptoms reflected the disease severity of the roots and bole. The foliar symptoms were more severe when basidioma were detected. Mean severity of foliar symptoms was 42%, 33% and 16% on seedlings with fully developed basidioma, basidioma primodia and without basidioma, respectively. Arrested growth and development were also observed on the seedlings. This was later followed by the death of the seedlings. By placing the inoculum block in close contact with three roots and the bole of the one year old oil palm in the field, IS-2S% infection of the bole tissues was achieved nine months after inoculation. The BSR associated symptoms observed were desiccation of the fronds and retardation of growth. BSR development tends to concentrate at the centre of the bole. Infected palms in the field were usually free from visible foliar symptoms until considerable damage had occurred in the bole region. Although all inoculated palms were infected, only 2S% of the infected palms exhibited foliar symptoms 22 months after inoculation. In vitro study showed that triazoles were significantly more effective than morpho lines, with an ECso values of 0.008-0.121 ppm a.i. and 1.939-2.944 ppm a.i., respectively. Total inhibition of mycelial growth by triazoles occurred at l-S ppm a.i. as compared to 2S0 ppm a.i. with morpho lines. Difenoconazole appeared to be the most active fungicide to the mycelial growth of G. boninense. However, the morpho lines generally exhibited better vapour phase activity than the triazoles against mycelial growth of Ganoderma. Penconazole and tridemorph showed good vapour phase activity and uniform colony inhibition. Uptake and efficacy of fungicides were detected by the bioassay on oil palm seedlings. Apparently penconazole had greater systemic activity than propiconazole and difenoconazole. Fungicides also have phytotoxicity in the order penconazole > propiconazole > difenoconazole. The greenhouse fungicide screening study on the bioefficacy indicated the potential curative activity of penconazole (O.S g a.I., preliminary experiment) and both difenoconazole and propiconazole (l.S g a.I., repeat experiment) against BSR during early infection stage. However, activity decreased with increase in degree of colonisation, especially on seedlings which have already produced basidioma.